The effect of written information and counselling by an advanced practice nurse on resilience in women with vulvar neoplasia six months after surgical treatment and the influence of social support, recurrence, and age: a secondary analysis of a multicenter randomized controlled trial, WOMAN-PRO II - Sabine Kofler; Andrea Kobleder; Stefan Ott; Beate Senn (BMC, 2020)
Abstract Background Women with vulvar neoplasia often complain about physical and psychological distress after surgical treatment. Lack of information and support can influence resilience. Whether an information-related intervention through an advanced practice nurse supports resilience and which other factors affect resilience in women with vulvar neoplasia has never been investigated. Methods The aims of this study were (a) to analyse whether counselling based on the WOMAN-PRO II program causes a significant improvement in the resilience scores of women with vulvar neoplasia compared to written information and (b) to identify the potential predictors of resilience. A randomized controlled trial was conducted in women with vulvar neoplasia (n = 49) 6 months after surgical treatment in four Swiss hospitals and one Austrian hospital. Analyses of resilience and its predictors were performed using a linear mixed model. Results Thirty-six women (intervention I, n = 8; intervention II, n = 28) completed the randomized controlled trial. In total, 13 women (26.5%) dropped out of the trial. The resilience score did not differ significantly between the two interventions three and six months after randomisation (p = 0.759). Age (b = .04, p = 0.001), social support (b = .28, p = 0.009), counselling time (b = .03, p = 0.018) and local recurrence (b = −.56, p = 0.009) were identified as significant predictors of resilience in the linear mixed model analyses. Conclusion The results indicate that the WOMAN-PRO II program as single intervention does not cause a significant change in the resilience scores of women with vulvar neoplasia 6 months after surgery. Predictors that promote or minimise resilience have been identified and should be considered when developing resilience programs for women with vulvar neoplasia. A repetition of the study with a larger sample size is recommended. Trial registration The WOMAN-PRO II program was registered in ClinicalTrials.gov NCT01986725 on 18 November 2013.